Studi karakteristik kimia minuman probiotik kombucha sari kulit nanas (Ananas comosus): Study of the chemical characteristics of probiotik baverage kombucha pineapple skin juice (Ananas comosus) - Budiandari, Rahmah Utami; Azara, Rima; Adawiyah, Ro’biatul; Prihatiningrum, Andriani Eko (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2023)
Kombucha is probiotic baverage, made from tea with sugar and starter SCOBY with time fermentation 4-14 days. Time of fermentation can be affects to physical and chemical properties of kombucha. This probiotic baverage has the potential to increase immunity and body resistance. Pineapple commonly consumed fresh or processed products, the part of pineapple that’s not consumed was skin and liver as 47%. The chemical component in pineapple skin was flavonoid, bromelain, 17,53% carbohydrates and 17% glucoses that can be used as kombucha. This research purpose to determine the effect of kombucha pineapple skin juice on the 7th day and 14th day fermentation. This research used a RBD with two factors, the first factor was sucrose concentration (5%, 10%, 15% and 20%) and second factor was starter SCOBY concentration (10% and 15%). This data were analyzed using ANOVA and minitab 17. The results on the 7th day showed sucore concentration has significant effect on the pH value, total Acid and TDS. Meanwhile starter SCOBY concentration had a signicantly effect on total acid and TDS but not signigicantly effect on the pH value. On the 14th day showed that sucrose and starter SCOBY has significantly effect to total acid, pH value and TDS.